Building Public Awareness of the Dangers of Plastic Waste and Management Strategies through Ecoless Socialization - Putri Yunita, Senia; Natalia Oroh, Angelica; Izzani Muhammad, Maghfir; Siti Nurilmi, Alifani; Andini, Meylita; Putri Sandrika, Aulia; Wahyu Febrianshinta, Amara; Tri Agustini, Rina; Sedionoto, Blego (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The construction of the National Capital City (IKN) in East Kalimantan has had a significant impact on waste management, especially plastic. With the increase in population due to this project, plastic waste in Sukaraja Village has increased, but access to landfills is very limited. As a result, the community prefers to burn waste, that are detrimental to the health of the environment. Good waste management is urgently needed to raise community awareness and create economic opportunities through recycling Objective : This activity aims to increase the knowledge of the community, especially mothers, about the negative impact of plastic waste on health and the environment Research Methods/ Implementation Methods : The Ecoless Socialization activity was conducted at the Sukaraja Village Office, involving 14 women representatives from the local hamlet. It included problem identification through observations and interviews, preparation of socialization materials, and implementation in three sessions: gymnastics together, material presentation, and video presentation of recycled products. Evaluation was conducted with pre-test and post-test Results : The results of the Ecoless activity in Sukaraja Village showed a significant increase in the knowledge of the participating mothers. The average pre-test score rose from 66.4% to 85% post socialization, reflecting a better understanding of the impact of plastic waste and how to reduce its use Conclusion/Lesson Learned : The Ecoless program was successful in increasing the community's understanding of the negative impacts of plastic waste and processing methods, with an average knowledge increase of almost 20%. Follow-up actions are suggested such as with entrepreneurship education, thus increasing awareness and benefits for the community